Odpowiedź :
Odpowiedź:
W(x) + P(x) = [tex]7x^{3}[/tex] - [tex]x^{2}[/tex] - 4x + 11
W(x) - P(x) = [tex]3x^{3}[/tex] - 13[tex]x^{2}[/tex] + 4x + 11
W(x) * P(x) = [tex]10x^{6}[/tex] + [tex]16x^{5}[/tex] - [tex]62x^{4}[/tex] + [tex]50x^{3}[/tex] + [tex]66x^{2}[/tex] - 44x
Szczegółowe wyjaśnienie:
W(x) = [tex]5x^{3}[/tex] - 7[tex]x^{2}[/tex] + 11
P(x) = 2[tex]x^{3}[/tex] + 6[tex]x^{2}[/tex] - 4x
W(x) + P(x) = ([tex]5x^{3}[/tex] - 7[tex]x^{2}[/tex] + 11) + (2[tex]x^{3}[/tex] + 6[tex]x^{2}[/tex] - 4x) = [tex]7x^{3}[/tex] - [tex]x^{2}[/tex] - 4x + 11
W(x) - P(x) = ([tex]5x^{3}[/tex] - 7[tex]x^{2}[/tex] + 11) - (2[tex]x^{3}[/tex] + 6[tex]x^{2}[/tex] - 4x) = [tex]3x^{3}[/tex] - 13[tex]x^{2}[/tex] + 4x + 11
W(x) * P(x) = ([tex]5x^{3}[/tex] - 7[tex]x^{2}[/tex] + 11) * (2[tex]x^{3}[/tex] + 6[tex]x^{2}[/tex] - 4x) =
= [tex]10x^{6}[/tex] + [tex]30x^{5}[/tex] - [tex]20x^{4}[/tex] - [tex]14x^{5}[/tex] - [tex]42x^{4}[/tex] + [tex]28x^{3}[/tex] + [tex]22x^{3}[/tex] + [tex]66x^{2}[/tex] - 44x =
= [tex]10x^{6}[/tex] + [tex]16x^{5}[/tex] - [tex]62x^{4}[/tex] + [tex]50x^{3}[/tex] + [tex]66x^{2}[/tex] - 44x